Diagnosis and control of the cucumber root rot causes using some chemical and biological agents - Hussein, Safaa Neamat (Journal of agricultural, environmental and veterinary sciences, 2020)
This research was aimed to identify the causal agent of the root rot disease of cucumber in some provinces of Iraq, and evaluate its pathogenicity and control it using beneficial bacteria of Serratia odorifera (So) and Enterobacter cloacae (Ec) which isolated from the rhizosphere of healthy cucumber plants, and using silicon (Si) and copper (Cu). The fungus Fusarium solani was predominant, while its percentage of appearance was 80.0% with frequency of 46.2%, Isolate Bfs- 1 was most virulent which prevent germination of the cucumber's seed overall in vitro compared to the control. The bacterial isolates D6 and Q10 exhibited 100% percentage of inhibition against the pathogen in vitro. Results of bacterial isolates identification using Vitiq2 Compact System showed that they belong to S. odorifera and E. cloacae respectively. Under greenhouse conditions the quadrant treatment (So+Ec+Si+Cu) was superior in controlling the disease, while it exhibited 100% percentage of seed germination compared to the negative control (Fungus alone) which achieved 58.0% and the percentage of disease incidence and severity were 9.0%, 3.5% respectively compared to the negative control which were 90.0%, 66.5% respectively. And the quadrant treatment exhibited significant increase of plant growth criteria represented by the dry width of plant, while it achieved 2.69 gm/plant compared to negative and positive control which were 0.85, 2.16 gm/plant respectively.
Keywords: Root rot disease of Cucumber; Fusarium sonai; Serratia odorifera; Enterobacter cloacae